A legislação aduaneira brasileira frente à desburocratização do comércio internacional - Katz, Ígor Santos (2017)
The standardization of international trade is a global reality where we find traces since the period of Lex Mercatoria until more recently, in the 1920s, the ICC (International Chamber of Commerce) wanted to harmonize the main terms of trade that afterward would be called as Incoterms (International Commercial Terms), given that the current version is the 2010 and include 11 terms (EXW, FCA, FAS, FOB, CFR, CIF, CPT, CIP, DAT, DAP e DDP). The are International Organization such as WCO (Word Customs Organization) and OECD (Organization for Economic Co-operational and Development, among others, working hard to harmonize the rule of international trade. Regarding the Brazilian rules and the harmonization of international trade rules, a great part of militate in the customs area believes that the standardization of basic proceeds of international trade will bring greater legal security on business practice and maybe would avoid some questions that sometimes seems to be peculiar to Brazilian market. Proof of this, occurs when the Brazilian buyer requires to the European or American seller to issue the commercial invoice in accordance with the Brazilian regulation in order to avoid customs penalties and extra costs in the process, such as storage and demurrage. In the relentless pursuit of trade simplification and good-faith in the international trade relation is when we actually looks in the subject with vision that the importer and exporter could have more predictability of the process of customs clearance